The Effect of Problem Based Learning and Teams Games Tournaments Model to Improve Competencies - Eko Swi Damarwan; Haryanto Haryanto; La Tara (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
This paper explores the potential of problem based learning and teams games tournaments model to improve students’ competencies. The objective of the study was to know the differences in the achievement of basic electrical and electronic competencies of students in terms of cognitive and psychomotor aspects using problem based learning model, teams games tournaments, and conventional learning. This was a quasi-experimental study. Instrument validity was measured through expert judgments and instrument reliability with Spearman Brown. Data collection used a pretest, a posttest, and skill observations. Data analysis techniques used one way ANOVA and a Tukey's post hoc test with a significance level of 0.05. The results revealed (1) differences in the achievement of basic electrical and electronic competencies of students in terms of cognitive and psychomotor aspects between using problem based learning, Teams Games Tournaments, and conventional learning, and (2) the results of the Tukey test showed the sequence of achievement of cognitive and psychomotor aspects of the best as follow: the model of teams games tournaments, problem based learning, and conventional learning.